2015
DOI: 10.3892/ijo.2015.3178
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-203 induces apoptosis by upregulating Puma expression in colon and lung cancer cells

Abstract: Abstract. The present study investigated the relationship between and the p53 upregulated modulator of apoptosis (Puma) in colon (HCT116) and lung cancer (A549) cells. Colon and lung cancer cell lines were selected for this study since a relationship between p53/miR-203 and p53/Puma has been established in both cancers. In the present study, adriamycin and nutlin-3 were used to activate p53, which induced both miR-203 and Puma expression in HCT116 cells. In contrast, HCT 116 cells with downregulated p53 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In the present study, we found that expression of miR‐203 significantly suppressed NSCLC cell growth, and decreased cell migration and invasion as reported in previous studies . However, overexpression of RGS17 reversed the miR‐203‐induced antitumor effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we found that expression of miR‐203 significantly suppressed NSCLC cell growth, and decreased cell migration and invasion as reported in previous studies . However, overexpression of RGS17 reversed the miR‐203‐induced antitumor effect.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found that expression of miR-203 significantly suppressed NSCLC cell growth, and decreased cell migration and invasion as reported in previous studies. (18,19,24,28,29) However, overexpression of RGS17 reversed the miR-203-induced antitumor effect. The bifluorescein test further verified that miR-203 integrated into the 3 0 -UTR of RGS-17 and post-transcriptionally downregulated RGS-17 expression.…”
Section: Discussionmentioning
confidence: 98%
“…PUMA also functioned through other Bcl-2 family members, such as Bcl-2, Bcl-XL and Bax (32). Although the specific mechanism for PUMA inducing apoptosis needs further investigation, it has been shown to be a promising new terget in gene therapy (33,34). The goal of this study was to explore the effect of combining Slug siRNA with X-ray irradiation on HSC3 and HSC6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…25,39 Moreover, miR-203 controls cell proliferation in haematopoietic malignancies by targeting ABL1 23 and induces apoptosis in colon and lung cancer cells by upregulating the expression of Puma. 40 However, the functions of miR-203 in Xinjiang Kazak ESCC remain unambiguous and warrant further studies.…”
Section: Discussionmentioning
confidence: 97%